2018
DOI: 10.3390/ijerph15122682
|View full text |Cite
|
Sign up to set email alerts
|

Association between Problematic Internet Use and Sleep Disturbance among Adolescents: The Role of the Child’s Sex

Abstract: Use of the Internet has become an integral part of daily life. Adolescents are especially at a higher risk of developing problematic Internet use (PIU). Although one of the most well-known comorbid conditions of PIU is sleep disturbance, little is known about the sex disparity in this association. This school-based survey in students of grades 7–9 was conducted to estimate the prevalence of PIU and sleep disturbance among Chinese adolescents, to test the association between PIU and sleep disturbance, and to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
(39 reference statements)
2
19
0
1
Order By: Relevance
“…While one of the included studies found no significant difference between males and females [ 36 ], another found that problematic internet use was higher for male participants [ 33 ]. On the contrary, three other studies showed that the prevalence of problematic internet use was higher for females [ 38 , 43 , 44 ]. Based upon the contradictory findings, additional research on the role of the adolescent’s sex could be enlightening; mood and sleep share common genetic ground, have a bidirectional relationship and females are more likely to experience mood disorders [ 64 ], thereby sleep may affected.…”
Section: Discussionmentioning
confidence: 88%
“…While one of the included studies found no significant difference between males and females [ 36 ], another found that problematic internet use was higher for male participants [ 33 ]. On the contrary, three other studies showed that the prevalence of problematic internet use was higher for females [ 38 , 43 , 44 ]. Based upon the contradictory findings, additional research on the role of the adolescent’s sex could be enlightening; mood and sleep share common genetic ground, have a bidirectional relationship and females are more likely to experience mood disorders [ 64 ], thereby sleep may affected.…”
Section: Discussionmentioning
confidence: 88%
“…Sleep quality and disturbances over the past month were assessed by the Chinese version of the Pittsburgh Sleep Quality Index (PSQI). The Chinese version of the PSQI has been validated [37] and has been extensively used [8,38] with Chinese adolescents. The survey assessed the 19-item PSQI, which consists of seven components containing subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbance, use of sleep medications, and daytime dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…El trastorno del sueño se ha estudiado desde diferentes perspectivas que abordan su vinculación con un UPI (Thomée, Härenstam y Hagberg, 2012;Park, 2014;Demirci, Akgönül y Akpinar, 2015;Kim et al, 2016;Tan et al, 2016;Li et al, 2017;De Vries et al, 2018;Do y Lee, 2018;Guo et al, 2018;Herlache, Lang DOI: http://dx.doi.org/10.22201/iibi.24488321xe.2020.82.58118 y Krizan, 2018; Kitazawa et al, 2018;Park et al, 2018;Yang et al, 2018;Kojima et al, 2019). El instrumento principal para su análisis ha sido mayoritariamente la Pittsburgh Sleep Quality Index (PSQI) (50 %).…”
Section: Trastorno Del Sueñounclassified